Cooperatives confronting the challenges of modern agriculture in Poland - Suchoń, Aneta (Przegląd Prawa Rolnego, 2018)
The aim of the article is to answer the question whether and to what extent the legal regulation of agricultural cooperatives, their organisation and functioning respond to the challenges of modern agriculture in Poland. It has been shown that following Poland’s accession to the European Union, the activity of Polish agricultural cooperatives has been focused not only on production but also on supporting the activity of co-op-producers of agricultural produce. As a result Polish agriculture has being developing well and, at the same time, in line with EU policies. By regulating agricultural cooperatives, their organisation and functioning, the legislator seeks to respond to the challenges of modern agriculture, although there is no doubt that further legislative changes are necessary.